Can Regional Employment Disparities Explain the Allocation of Human Capital Across Space? - Arntz, Melanie; Gregory, Terry; Lehmer, Florian (Regional Studies, 2014)
Arntz M., Gregory T. and Lehmer F. Can regional employment disparities explain the allocation of human capital across space, Regional Studies. This paper examines the determinants of skill-selective regional migration in a context where modelling the migration decision as a wage-maximizing process may be insufficient due to persistent employment disparities. Based on a Borjas-type framework it is shown that high-skilled workers are disproportionately attracted to regions with higher mean wages and employment chances as well as higher regional wage and employment inequalities. Estimates from a labour flow fixed-effects model and a general methods of moments (GMM) estimator show that these predictions hold, but only employment disparities induce a robust and significant skill sorting. The paper thus establishes a missing link about why employment disparities may actually be self-reinforcing.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Employment inequality; Gross migration; Migration selectivity; Regional disparities; Wage inequality